Analysis and future development of direct-to-handset satellite key technologies - SONG Yanjun; XIAO Yongwei; SUN Chenhua (Dianxin kexue)
The technology of direct-to-handset satellite is developing rapidly, which is the result of many factors such as the breakthrough of payload technology, the innovation in mobile phone technology, and the standards verification. Through the introduction of direct-to-handset satellite, two technical routes and three realization methods of direct-to-handset satellite were summarized. According to the technical problems of satellite-ground frequency sharing, space-borne antenna and space-borne base station, the key research contents were given based on the actual system and application scenarios. As the component of 5G communication and the basic of 6G communication, the future development of direct-to-handset satellite were discussed.